ApoM Suppresses TNF-α-Induced Expression of ICAM-1 and VCAM-1 Through Inhibiting the Activity of NF-κB - Gao, Ji-Juan (DNA Cell Biol, 2015)
To explore the anti-inflammatory effect of apolipoprotein M (apoM) on regulation of tumor necrosis factor-α (TNF-α)-induced expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) and further investigate the molecular mechanism of apoM in this process. We found that TNF-α could decrease expression of apoM and inhibitor of NF-κB-α (IκBα) in HepG2 cells. Overexpression of apoM caused a significant decrease of ICAM-1 and VCAM-1 expression, while it caused a significant increase of IκBα expression in HepG2 cells. Furthermore, the treatment with TNF-α could increase ICAM-1 and VCAM-1 expression, decrease IκBα protein expression, and increase nuclear factor-κB (NF-κB) activity, and these effects were markedly enhanced by small interfering RNA (siRNA)-mediated silencing of apoM in HepG2 cells. Our findings demonstrated that apoM suppressed TNF-α-induced expression of ICAM-1 and VCAM-1 through inhibiting the activity of NF-κB.